Risk of reinfection and severity with the predominant BA.5 Omicron subvariant China, from December 2022 to January 2023 - Jianpeng Cai; Haocheng Zhang; Kun Zhu; Feng Zhu; Yan Wang; Sen Wang; Faren Xie; Meng Zhang; Lili Rui; Shuhong Li; Ke Lin; Quanlin Xue; et al. (Emerging Microbes and Infections)
Data on reinfection in large Asian populations are limited. In this study, we aimed to evaluate the reinfection rate, disease severity, and time interval between the infections in the symptomatic and asymptomatic populations which are firstl infected with BA.2 Omicron Variant. We retrospectively included adult patients with COVID-19 discharged from four designated hospitals between 27 April 2021 and 30 November 2022, who were interviewed via telephone from 29 January to 1 March 2023. Univariable and multivariable analyses were used to explore risk factors associated with reinfection. A total of 16,558 patients were followed up, during the telephone survey of an average of 310.0 days, 1610 (9.72%) participants self-reported reinfection. The mean time range of reinfection was 257.9 days. The risks for reinfection were analysed using multivariable logistic regression. Patients with severe first infection were at higher risk for reinfection (aORs, 2.50; P < 0.001). The male (aORs,0.82; P < 0.001), the elderly (aORs, 0.44; P < 0.001), and patients with full vaccination (aORs, 0.67; P < 0.001) or booster (aORs, 0.63; P < 0.001) had the lower risk of reinfection. Patients over 60 years of age (aORs,9.02; P = 0.006) and those with ≥2 comorbidities (aORs,11.51; P = 0.016). were at higher risk for severe reinfection. The number of clinical manifestations of reinfection increases in people with severe first infection (aORs, 2.82; P = 0.023). The overall reinfection rate was 9.72%, and the reinfection rate of Omicron-to-Omicron subvariants was 9.50% at one year. The severity of Omicron-Omicron reinfection decreased. Data from our clinical study may provide clinical evidence and bolster response preparedness for future COVID-19 reinfection waves.